Patient-perceived responsiveness of primary care systems across Europe and the relationship with the health expenditure and remuneration systems of primary care doctors. (August 2017) - Murante, Anna Maria; Seghieri, Chiara; Vainieri, Milena; Schäfer, Willemijn L.A.
Abstract: Background: Health systems are expected to be responsive, that is to provide services that are user-oriented and respectful of people. Several surveys have tried to measure all or some of the dimensions of the responsiveness (e.g. autonomy, choice, clarity of communication, confidentiality, dignity, prompt attention, quality of basic amenities, and access to family and community support ), however there is little evidence regarding the level of responsiveness of primary care (PC) systems. Methods: This work analyses the capacity of primary care systems to be responsive. Data collected from 32 PC systems were used to investigate whether a relationship exists between the responsiveness of PC systems and the PC doctor remuneration systems and domestic health expenditure. Results: There appears to be a higher responsiveness of PC when doctors are paid via capitation than when they only receive a fee for services or a mixed payment method. In addition, countries that spend more on health services are associated with higher levels of dignity and autonomy. Conclusion: Quality, as measured from the patient's perspective, does not necessarily overlap with PC performance based on structure and process indicators. The results could also stimulate a new debate on the role of economic resources and PC workforce payment mechanisms in the achievement of quality goals, in this case related to the capacity of PC systems to be responsive. Highlights: Primary care systems differently perform in terms of responsiveness. Western countries are more responsive than Mediterranean or Eastern countries. Prospective mechanisms of payment of doctors is associated with the responsiveness. The higher is the total health expenditure the higher are Dignity and Autonomy scores. There is an association between private health expenditure and the responsiveness of primary care.